2004
DOI: 10.1606/1044-3894.324
|View full text |Cite
|
Sign up to set email alerts
|

Kinship Care and Permanence: Guiding Principles for Policy and Practice

Abstract: ith the implementation of the Adoption and Safe Families Act of 1997 (ASFA), which was designed to reduce the length of a child's stay in foster care by enforcing strict timeframes for movement to permanency, and the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 (PRWORA), which has decreased the number of families receiving welfare assistance, an even larger number of children may enter temporary or permanent care of the public child welfare system or may have additional barriers affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Such perceptions could contribute to a worker's decision to provide different services to kin and non-kin families. Children adopted by relatives often have a pre-adoptive risk history and are likely to exhibit behavioral problems kin adopters may not be prepared to manage (Lorkovich et al, 2004). It is vital that kin adopters also receive comprehensive preparation to promote positive child outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Such perceptions could contribute to a worker's decision to provide different services to kin and non-kin families. Children adopted by relatives often have a pre-adoptive risk history and are likely to exhibit behavioral problems kin adopters may not be prepared to manage (Lorkovich et al, 2004). It is vital that kin adopters also receive comprehensive preparation to promote positive child outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Professional beliefs about the use of kinship caregivers can influence worker decisions and the way services are provided. In a 3-year exploratory study on the barriers of kinship care, Lorkovich, Piccola, Groza, Brindo, and Marks (2004) found that workers, administrators, and policy makers experienced difficulty separating their concerns and attitudes about the biological family from kinship caregivers. These attitudes about kinship homes may impede worker's willingness to encourage or support kinship placements.…”
Section: Caseworker Attitudesmentioning
confidence: 99%
“…Some relatives choose to parent informally because adoption would require that they gain consent from the child's biological parent(s) and/or show that the child's biological parents were unfit (Geen, 2003;Aldous, 1998), which could strain existing family relationships. Others may not understand or value the legal distinctions between adoption and guardianship, and/or the benefits available to adoptive families, such as adoption subsidies and Medicaid coverage for families adopting eligible children from foster care (Lorkovich et al, 2004). In addition, some grandparents may prefer to provide care informally because they hold out hope that their adult children will at some point resume principal responsibility for the child or they are unsure about whether their own current or future health status will permit them to continue to parent.…”
Section: Caregiving By Relativesmentioning
confidence: 99%
“…While relative adoption from foster care has received some limited academic focus (Ryan, Hinterlong, Hegar, & Johnson, 2010;Lorkovich, Piccola, Groza, Brindo, & Marks, 2004;Howard & Smith, 2003), private adoptions by relatives have received virtually no attention, and indeed even counts of this population are scarce (Placek, 2007), though they are more numerous than kin adoptions from foster care (Vandivere, Malm, & Radel, 2009). Research related to the well-being of the far greater number of children cared for by relatives without the structure of a legal adoption, that is children "informally adopted" by their kin, is also quite limited (Ehrle, Geen, & Clark, 2001).…”
Section: Introductionmentioning
confidence: 99%